Facile synthesis of high density carbon nanotube array by a deposition-growth-densification process. (April 2017) - Zhang, Kai; Li, Taotao; Ling, Lin; Lu, Huifen; Tang, Lei; Li, Chaowei; Wang, Liangjie; Yao, Yagang
Abstract: In this work, we developed a deposition-growth-densification process to produce high density vertically aligned carbon nanotube (VACNT) array. The key to increase the density of VACNT array was the liquid-induced densification process, which not only gave the VACNT array densely packed structure, but also exposed as much substrate as possible for later VACNT growth. During the process, the cycling of catalyst deposition, CVD growth and densification process made new VACNT array continuously grown on the substrate exposed in the liquid-induced process. The density of VACNT array was increased gradually and controllably by altering the cyclic times. For now, a CNT filling factor of 30.84% was achieved. The engineering of the density and the compatibility with other techniques made it promising for the applications of carbon nanotube. Graphical abstract: